Translation and the Intersection of Texts, Contexts and Politics : Historical and Socio-Cultural Perspectives - Albakry, Mohammed (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
'This varied and erudite collection succeeds in widening our understanding of how context, that dynamic element of discourse that encompasses both external and internal factors, must be taken into account as an important mediating aspect of the translational act and its reception.' -- Jeanne Garane, Professor of French and Comparative Literature, University of South Carolina, USA This book analyzes the impact of historical, political and sociocultural contexts on the reading, rewriting and translating of texts. The authors base their arguments on their experiences of translating or researching different text types, taking in fiction, short stories, memoirs, religious texts, scientific treatises, and news reports from a variety of different languages and cultural traditions. In doing so they cover a wide range of contexts and time periods, including Early Modern Europe, post-1848 Switzerland, nineteenth-century Portugal, Egypt in the early twentieth century under British colonial rule, Spain under Franco's dictatorship, and contemporary Peru and China. They also consider the theoretical and pedagogical implications of their conclusions for translation students and practitioners. This edited collection will be of great interest to scholars working in translation studies, applied linguistics, and on issues of cultural difference. Mohammed Albakry is Professor of English and Applied Linguistics and Affiliate Faculty in the Literacy Studies Ph.D. Program at Middle Tennessee State University, USA. He has authored numerous refereed articles and co-edited the drama anthology Tahir Tales: Plays from the Egyptian Revolution (2016). He is also a practicing translator and was awarded a 2014 National Endowment for the Arts Translation Fellowship.
Keywords: Linguistics.; Globalization.; Sociolinguistics.; Translation and interpretation.; Multilingualism.; Language policy.; elektronické knihy; electronic books